Past and current approaches to decimal numbers in Dutch primary school mathematics textbooks - Zanten, Marc van; Heuvel-Panhuizen, Marja van den (NOMAD Nordic Studies in Mathematics Education, 2015)
In the Netherlands, most contemporary textbook series for primary school mathematics education are influenced by the so-called Realistic mathematics education (RME) reform. This reform dates back to the 1970s. In the study described in this paper we investigated what this reform means for the approach to decimal numbers. We analyzed how this content domain is treated in a contemporary RME-oriented textbook series and two pre-RME textbook series. Our study revealed that most, although not all, of the RME characteristics included in our analysis framework were found to be present in the researched contemporary RME-oriented textbook The world in numbers (2009). Furthermore, it was found that onsets of several RME characteristics were already present in the two older textbooks, New arithmetic (1958) and Functional arithmetic, (1969) that date from before the RME reform started.